Applied Mindfulness for Physician Wellbeing: A Prospective Qualitative Study Protocol - Weisbaum, Elli; Chadi, Nicholas (Frontiers in Public Health, 2022)
Background Physician burnout has significant adverse impacts on the wellbeing of individual physicians, and by extension the healthcare delivery systems of which they are part. Mindfulness is consistently cited as a pragmatic approach to effectively address burnout and enhance physician wellbeing. However, very few empirical studies have been published on Mindfulness Based Interventions (MBIs) for physicians. Moreover, the majority of these studies have been quantitative, leaving a gap in understanding the practical application of mindfulness in the context of physicians' daily lives. Objectives This paper outlines the rationale, development and design of a novel prospective qualitative study examining the acceptability, feasibility, and pragmatic application of a mindfulness intervention for physician wellness. Methods The study will be conducted in three groups of at least 8 practicing physicians from a broad range of medical specialties at a tertiary care hospital in a large urban center in Eastern Canada. The intervention will consist of an innovative program based on the teachings of internationally renowned scholar and Zen Master Thích Nhãt Hạnh. It will include 5 weekly 2-h mindfulness sessions delivered by two health providers trained in mindfulness and in the teachings of Thich Nhat Hanh. The primary outcome measure will be an in-depth Thematic Analysis of post-program semi-structured interviews. Field data will also be collected through participant observation. The study will be theoretically grounded within the interpretive paradigm utilizing “the Mechanisms of Mindfulness Theory”. An external advisory committee formed by four senior members of Thích Nhãt Hạnh's community will provide guidance across all phases of the study. Discussion Our innovative approach provides a new framework to further understand the mechanisms by which mindfulness interventions can impact physician wellbeing, and by extension their patients, colleagues, and broader healthcare systems. Through a clear articulation of the rigorous application of accepted procedures and standards used in our protocol, this paper seeks to provide a roadmap for other researchers who wish to develop further studies in this area. Lessons learned in the preparation and conduction of this study can be applied to other healthcare contexts including non-physician health provider wellbeing, clinical care, and population-level mental health.